Poesia operativa. Per un approccio do it alla poesia italiana: L’estetica do it in Italia (TEST Ticontre. Theory Text Translation, 2017)
A do it critical approach aims to underline the rhetorical devices which are active in a contemporary “operational” text. By that expression, my purpose is to qualify poems which encourage the readers to carry out an autonomous act. Poetry can therefore represent a sort of instructions manual. It can be used as if it was a music arrangement, in case it provides the reader with the information about spatial coordinates and an assembly kit of everyday objects in order to carry out a certain action. Operational poetry tries to inform the reader about what exactly he needs to fulfill deeds, by listing everyday object, employing second-person-conjugated verbs, infinitive and imperative forms. It neither differs from performative poetry because it does not require the artist himself to perform and from paraenesis as it does not try to lure and convince the readers to do anything nor deals with moral issues.